Pengembangan Media Digital Interaktif Berbasis Kearifan Lokal Tarian Jaran Eblek untuk Meningkatkan Keterampilan Berpikir Kritis Siswa pada Materi Sistem Gerak Manusia - Shofa Rahayu; Yeri Sutopo; Agus Yuwono (Khatulistiwa: Jurnal Pendidikan dan Sosial Humaniora, 2024)
This study aims to develop interactive digital media based on the local wisdom of the Jaran Eblek dance as an innovative learning tool to improve the critical thinking skills of elementary school students, especially in the material of the human movement system. The background of this study is based on the importance of integrating local culture in science learning so that students not only gain a cognitive understanding of concepts, but also internalize the values ​​of local wisdom. The development model used is ADDIE, which includes five stages, namely Analysis, Design, Development, Implementation, and Evaluation. The research subjects consisted of 5 media experts, 5 material experts, 15 teachers, and 85 sixth grade elementary school students who became the trial group. The research instruments were in the form of validation sheets, practicality questionnaires, and critical thinking skills tests designed according to learning indicators. The validation process carried out by media experts resulted in an average score of 4.74 with a very feasible category, while the assessment from material experts obtained a score of 4.47 with a very feasible category. The practicality test involving teachers and students showed that the interactive digital media was included in the very practical category with a score of 92.29%. Meanwhile, the effectiveness test using N-Gain analysis showed that the experimental class using the media obtained a score of 76.94% with an effective category, while the control class only achieved 33.13%. The results of further statistical tests proved a significant difference (p < 0.05) between the two classes, which indicates that this interactive digital media is able to have a positive impact on improving students' critical thinking skills. Thus, this study concludes that interactive digital media based on local wisdom of the Jaran Eblek dance is feasible, practical, and effective for use in learning.